Hijab Cosplay sebagai Panggung Sosial: Perspektif Dramaturgi pada Grup Hijab Cosplay South Borneo - Riski, Ahmad Sawban; Khairussalam (Prodi Sosiologi FISIP ULM, 2026)
Hijab cosplay is a form of self-presentation of Muslim women who present fictional characters through costumes and visual appearance, but still maintain Islamic law, thus reflecting the dynamics of interaction between popular culture and religious identity. This research aims to find out how the self-presentation of hijab cosplay is on the front stage, back stage, and in impression management on the front stage. In this context, impression management is used by actors to show impressions to the audience. This research uses a phenomenological qualitative method with observation, semi-structured interviews, and documentation as data collection techniques. The results showed that in the front stage, hijab cosplay performed the character maximally by paying attention to the aspects of dramaturgy. On the backstage, some maintain consistency, while others show different behavior. As for impression management, it is done through adaptation of appropriate character selection without eliminating religious identity, such as replacing a wig with a hijab, to create the desired self-image. This research contributes a new understanding of hijab cosplay by reading the hijab cosplay stage from the perspective of Erving Goffman's dramaturgy theory as a unique form of self-presentation. The findings can be a reference for future research that wants to examine identity and impression management in the context of popular culture and religiosity.